Comparative medical characteristics of ZDF‐T2DM rats during the course of development to late stage disease. Issue 3 (25th September 2018) - Pang, Yun‐Li; Hu, Jing‐Wen; Liu, Guang‐Long; Lu, Shuai‐Yao
Abstract: Background: There are few reports on the comparative medical characteristics of type 2 diabetes models in late stage. An analysis of comparative medical characteristics of Zucker diabetic fatty type 2 diabetes mellitus (ZDF‐T2DM) rats during the course of development to late stage disease was performed. Methods: In this study, ZDF rats were fed with high‐sugar and high‐fat diets to raise the fasting blood glucose, and develop of type 2 diabetes. At the late stage of T2DM, the preliminary comparative medical characteristics of the T2DM model were analyzed through the detection of clinical indicators, histopathology, related cytokine levels, and insulin‐related signaling molecule expression levels. Results: In the T2DM group, the fasting blood glucose was higher than 6.8 mmol/L, the serum insulin, leptin, and adiponectin levels were significantly decreased, and glucose intolerance and insulin resistance were measured as clinical indicators. Regarding pathological indicators, a large number of pancreatic islet cells showed the reduction of insulin secretion, resulting in damaged glycogen synthesis and liver steatosis. At the molecular level, the insulin signal transduction pathway was inhibited by decreasing the insulin receptor substrate 1 (IRS1), insulin receptor substrate 2 (IRS2), phosphatidylinositol 3 kinase (PI3K), and glycogen synthesis kinase 3β (GSK‐3β) expression levels. Conclusion: The results show that the ZDF/T2DM rats have typical clinical, histopathological, and molecular characteristics of human T2DM and thus can be used as an effective model for T2DM drug development and treatment of advanced T2DM.